2022
DOI: 10.1055/s-0042-1755558
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Saliva Composition: Parathyroid Hormone-Related Protein, Total Protein, and Secretory Immunoglobulin A (sIgA) in Rattus norvegicus with Stunted Growth

Abstract: Objective This study aimed to determine total protein, secretory immunoglobulin A (sIgA) and parathyroid hormone-related protein (PTHrP) levels in the saliva of rats with stunted growth. Materials and Methods Experimental laboratory research with a pre-and posttest control group design was conducted. Seventeen albino rats (Rattus norvegicus) were divided into the control group (eight rats) and the treatment group (nine rats). Rats in the treatment group were exposed to aflatoxin B1 5µg/kg orally for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…The child exhibited enamel hypoplasia, incomplete root formation, and delayed tooth eruption in the permanent dentition, all attributed to untreated hypocalcemia during tooth development. 16 In comparison to our findings, study by Tedjosasongko et al, 17 revealed significantly lower levels of PTHrP, sIgA, and total protein in the saliva of the treatment group compared to the control group (p < 0.05). However, in contrast to our results, Wulandari et al, 18 found no significant correlation between calcium intake and delayed eruption of permanent canines, with a p-value exceeding 0.05.…”
Section: Discussioncontrasting
confidence: 85%
“…The child exhibited enamel hypoplasia, incomplete root formation, and delayed tooth eruption in the permanent dentition, all attributed to untreated hypocalcemia during tooth development. 16 In comparison to our findings, study by Tedjosasongko et al, 17 revealed significantly lower levels of PTHrP, sIgA, and total protein in the saliva of the treatment group compared to the control group (p < 0.05). However, in contrast to our results, Wulandari et al, 18 found no significant correlation between calcium intake and delayed eruption of permanent canines, with a p-value exceeding 0.05.…”
Section: Discussioncontrasting
confidence: 85%